Digital Library Facilities and Infrastructure Management YSU towards Bureaucratic Reform System 4.0. in the New Normal Era - Sumarjono Sumarjono (Metafora: Education, Social Sciences and Humanities Journal, 2023)
This study aims to describe the management of digital library facilities and infrastructure at Yogyakarta State University (YSU) in the context of bureaucratic reform 4.0. in the new normal. The Covid-19 pandemic is considered a strategic momentum for implementing bureaucratic reforms that the Indonesian government has put forward in the 2000s. This research uses descriptive-qualitative to describe and analyze how the digital library has implemented a 4.0-based facilities and infrastructure management system. The three re-search results obtained are as follows. First, the YSU digital library has implemented facili-ties and infrastructure management according to institutional needs so that its service facili-ties meet international standards. Second, digital library facilities and infrastructure man-agement is a form of bureaucratic reform adaptive to change as projected through the In-dustrial Revolution 4.0. Third, the bureaucratic reform in the YSU digital library had a sig-nificant impact on good governance. During the Covid-19 pandemic, continued to provide the best service for the academic needs of students.